2017
DOI: 10.1590/2179-8087.018915
|View full text |Cite
|
Sign up to set email alerts
|

Decomposição e Atividade Microbiana da Serapilheira em Coberturas Florestais no Sul do Espírito Santo

Abstract: RESUMOO processo de decomposição de serapilheira deve ser amplamente estudado por se tratar de um fator-chave na manutenção e ciclagem de nutrientes nos ecossistemas. Este estudo teve como objetivos: avaliar a decomposição, a liberação de nutrientes e a atividade microbiana da serapilheira em coberturas florestais de floresta secundária, Acacia mangium, Sapindus saponaria e Hevea brasiliensis, no sul do Espírito Santo. A decomposição da serapilheira e a liberação de nutrientes foi quantificada por meio de litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
6
0
12
Order By: Relevance
“…The decomposition curve obtained, with initial peak and subsequent smoothing, followed negative exponential simple model. Similar results were also verified by Silva et al (2013) and Grugiki et al (2017) in Atlantic Forest in southern state of Espírito Santo. Guimarães et al (2009) and Sena et al (2015) reported that nonlinear models are the best to describe biological parameters, since these parameters have hardly linear behavior.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The decomposition curve obtained, with initial peak and subsequent smoothing, followed negative exponential simple model. Similar results were also verified by Silva et al (2013) and Grugiki et al (2017) in Atlantic Forest in southern state of Espírito Santo. Guimarães et al (2009) and Sena et al (2015) reported that nonlinear models are the best to describe biological parameters, since these parameters have hardly linear behavior.…”
Section: Discussionsupporting
confidence: 89%
“…The monitoring of litter decomposition in litterbags showed that the leaf decomposition rate observed in the period under study is in accordance with that estimated by Anderson et al (1983) in neotropical forests, which varies from 1.1 to 1.7. However, the value Gomes Júnior D, Caldeira MVW, Klippel VH, Mendonça ES, Delarrmelina WM, Godinho TO et al found is above that observed by Silva et al (2013) and Grugiki et al (2017), both in Seasonally Dry Tropical Forest and in the secondary succession stage in Southern state of Espirito Santo. These variations are expected, since there is no homogeneity among tropical forest fragments in their attributes, either edaphic, climatic or biological.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although treatments were composed of different amount of species, the proportion of successional groups was the same for all treatments. The amount of litter on the soil surface can vary depending on the composition of species, successional stage, and intensity of forest cover (Caldeira et al, 2008;Grugiki et al, 2017). Therefore, the use of the same proportion of successional groups in the present study might have caused a similar response in the analyzed treatments.…”
Section: Accumulated Litter Biomassmentioning
confidence: 71%
“…Tratamentos k (g g -1 dia) t Avaliando a decomposição da serapilheira foliar, Pinto et al (2016) estimaram tempo de meia-vida de aproximadamente 433 dias. Já Grugiki et al (2017), quantificaram para Acacia mangium um tempo de meia-vida de aproximadamente 497 dias. Essa diferença nos resultados está relacionada aos fatores como a fauna e condições ambientais do local.…”
Section: Ecologia E Nutrição Florestal/ecology and Forest Nutrition unclassified